Mối quan hệ giữa phong cách lãnh đạo định hướng trách nhiệm xã hội và hiệu suất bền vững doanh nghiệp: Nghiên cứu thực nghiệm tại Đông Nam Bộ, Việt Nam - Lê Thanh, Tiệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study aims to examine the relationship between a corporate social responsibility-oriented leadership style and the corporate sustainable performance of small and medium-sized enterprises (SMEs) in the Southeast region of Vietnam. The study evaluates the direct impact of a corporate social responsibility-oriented leadership style on corporate sustainable performance in SMEs and examines the mediating relationship through three mediating variables: stakeholder engagement, internal activities socialization responsibility, and corporate social responsibility communication activities. The results show that a corporate social responsibility-oriented leadership style has a positive influence on corporate sustainable performance, and these three mediating factors play an important role in supporting the corporate social responsibility-oriented leadership style to achieve corporate sustainable performance. Additionally, transformational leadership theory is used to inform the issues studied. Quantitative data was collected from 508 surveys of mid- and senior-level managers at SMEs. The quantitative method of non-probability sampling was employed in this study. From this, the research provides management implications for business administrators, helping managers develop an overall strategic production orientation and providing tools to help increase corporate sustainable performance.
Keywords: Corporate social responsibility-oriented leadership; Sustainable performance; Stakeholder engagement; Internal activities socialization corporate social responsibility; Corporate social responsibility communication activities